Evaluation of the In Vitro Antimicrobial Activity of Ethanolic Extracts Derived from Leaves Of Camellia japonica Cultivars (Theaceae) Against Enterobacter cloacae Strain - Kharchenko, Igor; Tkachenko, Halyna; Buyun, Lyudmyla; Kurhaluk, Natalia; Góralczyk, Anna; Maryniuk, Myroslava; Tomin, Władimir; Osadowski, Zbigniew (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2019)
The increasing incidence of antibiotic resistance among bacterial and fungal pathogens necessitates plants as an alternative therapy in restricting the resistant infectious organisms. The present study was undertaken to determine the antibacterial activity of ethanolic extracts derived from the leaves of Camellia japonica cultivars. The aim of the presented study was to assess the in vitro antimicrobial activity of ethanolic extracts derived from the leaves of C. japonica ’Kramer’s Supreme’, ’C.M. Wilson’, ’La Pace’, ’Mrs. Lyman Clarke’, ‘Benikarako’, ‘Fanny Bolis’ against clinical cefuroxime-resistant Enterobacter cloacae strain. Ethanolic extracts were prepared by freshly crushed leaves and evaluated for their antimicrobial activity against Enterobacter cloacae strain locally isolated using disc diffusion assay. Among the six plant extracts screened, C. japonica ’Mrs. Lyman Clarke’ exhibited the highest inhibitory zones against the tested strain (the mean value of the zone of inhibition was 12.5 ±0.7 mm). The least activity is attributed to C. japonica ’La Pace’ extract. Based on our current investigations it can be concluded that C. japonica and its cultivars possess a mild antibacterial efficacy. This mild activity on the E. cloacae, Gram-negative organisms, is most likely due to the protective nature of the outer membrane of their cell walls. It may also be assumed that the antimicrobial potential of various samples of these plants might be due to a wide variety of compounds present in these plants. The findings reported herein give scientific credence to the traditional uses of these plants and suggest that extracts derived from the leaves of C. japonica and its cultivars merit further phytochemical study as natural antibiotics to identify the secondary metabolites.